RETRACTED: The Role of HOTAIR/miR-148b-3p/USF1 on Regulating the Permeability of BTB - Sa, Libo; Li, Yan; Zhao, Lini; Liu, Yunhui; Wang, Ping; Liu, Libo; Li, Zhen; Ma, Jun; Cai, Heng; Xue, Yixue (Frontiers in Molecular Neuroscience, 2017)
Homeobox transcript antisense intergenic RNA (HOTAIR), as a long non-coding RNA (lncRNA), has been considered to play critical roles in the biological properties of various tumors. The purposes of this study were to investigate the role and possible molecular mechanisms of HOTAIR in regulating the permeability of BTB in vitro. Our present study elucidated that the expressions of HOTAIR and upstream stimulatory factor 1 (USF1) was up-regulated, but miR-148b-3p was down-regulated in glioma microvascular endothelial cells (GECs). Knockdown of HOTAIR could increase the permeability of BTB as well as down-regulated the expressions of tight junction related proteins ZO-1, occluding, claudin-5, but up-regulated miR-148b-3p expressions in GECs. Meanwhile, dual-luciferase reporter assays demonstrated that HOTAIR was a target RNA of miR-148b-3p. Furthermore, overexpression of miR-148b-3p increased the permeability of BTB by down-regulating the expressions of tight junction related proteins and upstream stimulatory factor 1 (USF1) in GECs, and vice versa. And further result revealed USF1 was a target of miR-148b-3p. Silence of USF1 increased the permeability of BTB duo to their interaction with the promoters of ZO-1, occludin and claudin-5 in GECs. Taken together, our finding indicated that knockdown of HOTAIR increased BTB permeability via binding to miR-148b-3p, which further reducing tight junction related proteins in GECs by targeting USF1. Thus, HOTAIR will attract more attention since it can serve as a potential target of drug delivery across BTB and may provide novel strategies for glioma treatment.